Hyla nana (Dwarf Treefrog). - Ponssa, María Laura (2005)
ARGENTINA: TUCUMÁN: Monteros, Capitán Cáceres (27°12’S - 65°38’W). 03 March 2005. M. L. Ponssa. Verified by G. Scrocchi. Herpetological Collection Fundación Miguel Lillo, San Miguel de Tucumán, Argentina (FML 16064-70, adult males; 16071 adult female). The species range includes diverse areas of Brazil, Paraguay, Bolivia, Uruguay, and the Argentine provinces of Salta, Formosa, Chaco, Santa Fe, Misiones, Corrientes, Entre Ríos and Buenos Aires (Lavilla et al. 2000. Categorización de los anfibios y reptiles de la República Argentina. Asociación Herpetológica Argentina: 11-34). First province record and the southernmost in the western range; extends the known distribution about 550 km S from its closest record, Aguas Blancas in Salta (Langone & Basso, 1987. Com. Zool. Mus. Hist. Nat. Montevideo, 11 [164]: 1-17). Animals were calling on low vegetation of temporal ponds at border of the Provincial Road 324. Historically this area corresponds to montane forests (Andean Yungas), but at present is strongly disturbed by crops and human settlements.